IMPROVING STUDENTS' MATHEMATICAL REPRESENTATION SKILLS IN SYSTEMS OF LINEAR EQUATIONS IN TWO VARIABLES THROUGH GEOGEBRA-BASED STEM APPROACHES: A QUASI-EXPERIMENTAL STUDY - Nugroho, Hery; Septianisha, Nurul Indah (Jurnal Pendidikan Matematika dan IPA, 2025)
Many studies have attempted to improve students' mathematical representation skills in learning systems of linear equations in two variables (SLETV). However, few studies have attempted to improve students' mathematical representation skills using the GeoGebra-based STEM approach, particularly in solving the SLETV topic. This research aims to analyze the effectiveness of the GSA model in improving students' mathematical representation skills on the SLETV topic. This type of research is quantitative with a quasi-experimental nonequivalent control group design to compare the effectiveness of the GeoGebra-based STEM approach (GSA) model with the conventional learning (CL) model. The research subjects consisted of 32 students, the experimental group, and 29 students, the control group, randomly selected from one of the private junior high schools in Yogyakarta. The data analysis technique uses the Independent Sample T-test and the N-Gain score. Based on the analysis results, the research shows that the GSA model is more effective than the CL model in improving students' mathematical representation skills on the SLETV topic. The results of this study offer an innovative model for education practitioners and policymakers in an effort to improve students' mathematical representation skills based on multidisciplinary and ICT in the 21st century.